APLIKASI MIKROFOTOGRAFI UNTUK MENGEKSPLORASI JENIS-JENIS CYANOPHYTA - Widodo, Widodo (Jurnal Florea, 2014)
Archiving and dissemination of data , techniques, and observations of Cyanophyta required for optimization of succesfully low plant systematics studies. This paper aims to present the preparation techniques and the results of Cyanophyta algae observing with light microscope and digitaly camera. Sources accurate specimen was also informed by the author repeatedly experience in organizing learning plant systematics. Preparation and microscopic observation Cyanophyta consists of preparation of accurate source of specimens , microscopic observation to obtain optimum picture of the object and focus , shooting or recording images using a digital camera. The image files are stored and are equipped with a scale.Results of preparation , observation and shooting showed that cells and colonies all Cyanophyta (Oscillatoria , Anabaena , Nostoc ) has a similar size range that requires preparation to optimize the use of the same light microscop . Cells of Cyanophyta colonies can be seen clearly in the eyepiece magnification of 10x and 40x objective. Less than that magnification, The thalus of Cyanophyta difficult to observe because of the relatively small cell size compared to the size of eukaryotic cells. By shooting with digitaly camera, microscopy observation images can be captured as digital specimen. Observing the digitaly specimen does not change depending on season and time. The digital images can also be analyzed and studied further. Keyword : microphotography, digitaly specimen, cyanophyta , low plant systematics